2022
DOI: 10.1542/neo.23-10-e677
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Embryopathies

Abstract: Diabetic embryopathy is defined as congenital anomalies that are linked to maternal diabetes. The association between diabetes and fetal, neonatal, and long-term complications is well-established. These complications include organ or structural maldevelopment, fetal growth abnormalities, and learning/psychiatric comorbidities. Recent studies have elucidated the pathophysiology behind these conditions and outlined new management approaches. Caudal regression syndrome, also known as sacral agenesis, is a well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Additionally, many studies have reported significant associations of maternal obesity with congenital heart defects, neural tube defects and genitourinary defects [ 52 , 53 , 54 ]. Diabetes mellitus is a well-established direct cause of birth defects through mechanisms that affect the growing embryo, known as diabetic embryopathy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many studies have reported significant associations of maternal obesity with congenital heart defects, neural tube defects and genitourinary defects [ 52 , 53 , 54 ]. Diabetes mellitus is a well-established direct cause of birth defects through mechanisms that affect the growing embryo, known as diabetic embryopathy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to blood glucose, embryo development also depends on the levels of cholesterol, triglycerides, and oxidative stress. 14 Oxidative stress can be teratogenic, and apoptosis after oxidative stress is related to diabetic embryopathy. Polyphenols can serve as antioxidants.…”
Section: Effects Of Polyphenols On Mothers With Maternal Diabetes And...mentioning
confidence: 99%
“…13 Maternal diabetes, whether T1DM or T2DM, can increase the risk of congenital anomalies and is a complication referred to as “diabetic embryopathy”. 14 Malformations may occur during the first 10 weeks of pregnancy (the early-organogenesis period), and almost any organ system can be affected, especially the cardiac, musculoskeletal, and central nervous systems. 15 In contrast, although the risks for adverse consequences are far lower with GDM than with PGDM, GDM can cause several perinatal complications, such as stillbirth, perinatal death, metabolic syndrome, T2DM, and cardiovascular disease; the earlier the onset, the higher the severity.…”
Section: Introductionmentioning
confidence: 99%